The Views and attitudes of female church goers towards HIV/AIDS and related preventative measures : a preliminary study - Sibuyi, Lorna Precious (University of Limpopo (Medunsa Campus), 2009)
HIV/AIDS is increasing at a fast rate. Increasing numbers of women worldwide are being infected with HIV, the virus that causes AIDS. Condoms, abstinence and faithfulness have been suggested to prevent the further spread of HIV infection. The present study adopted a qualitative approach to explore the views and attitudes of female church goers towards HIV/AIDS and its preventative measures. The results indicated that they view HIV/AIDS as a fatal disease which cannot be cured by medical means, and it is caused by unprotected sex when an individual engages in sexual intercourse with someone infected with HIV. They all know that condoms are an effective form of prevention. Despite all their knowledge, however, they feel powerless, unsafe, and hopeless regarding effective HIV control and prevention due to their partners’ resistance in respect of condom usage. Church ministers should be more sensitive to the inequalities that exist in marriages and should be careful in their preaching of submission and obedience of women towards men. Church ministers should present their sermons in a way that fosters equalities and the practice of safe sex. Finally, it is also recommended that the younger generation, both males and females should be educated about gender equality during their Sunday school and youth programmes. These programmes should include teachings about gender equality, practice of safe sex, faithfulness and abstinence. Should this be done effectively the new generation could hopefully operate from a different frame of reference as opposed to the current generation whose value systems and norms are outdated and discriminatory.
Thesis (MSc.(Clinical Psychology))--University of Limpopo, 2009.
Keywords: HIV/AIDS; Church goers; HIV infections